2014
DOI: 10.1016/s1473-3099(14)70966-1
|View full text |Cite
|
Sign up to set email alerts
|

Pre-entry screening programmes for tuberculosis in migrants to low-incidence countries: a systematic review and meta-analysis

Abstract: Wellcome Trust, UK National Institute for Health Research, Medical Research Council, Public Health England.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 26 publications
3
73
1
1
Order By: Relevance
“…The detection of one active case among 299 screened contacts of patients with active EPTB also compares favourably to other screening strategies for active TB 8. By comparison, screening for abdominal aortic aneurysms over the age of 65 identified <1% of men eligible for yearly surveillance,9 cervical cancer screening identifies ∼7% of those with abnormal smears10 and bowel cancer screening identified ∼2% 11…”
Section: Screening Contacts Of Patients With Extrapulmonary Tb For Lamentioning
confidence: 99%
“…The detection of one active case among 299 screened contacts of patients with active EPTB also compares favourably to other screening strategies for active TB 8. By comparison, screening for abdominal aortic aneurysms over the age of 65 identified <1% of men eligible for yearly surveillance,9 cervical cancer screening identifies ∼7% of those with abnormal smears10 and bowel cancer screening identified ∼2% 11…”
Section: Screening Contacts Of Patients With Extrapulmonary Tb For Lamentioning
confidence: 99%
“…A systematic review 6 published in 2014 showed that, in pre-entry screening of migrants before travel to low-incidence countries, the largest number of cases was detected when screening was done in high-incidence countries. One-off pre-entry screening for active tuberculosis in migrants will detect only disease prevalent at the time of screening.…”
Section: Introductionmentioning
confidence: 99%
“…Few linked data are available for incident tuberculosis after migration to low-incidence countries in populations screened before entry, and even fewer data are available for risk factors for subsequent development of disease in this screened population. Investigators in previous studies focused on prevalent cases detected during pre-entry screening, 6 used national tuberculosis notification data alone with no linkage to pre-entry screening records, 7 or followed up a selected cohort of individuals from a few countries or subnationally after arrival 8, 9, 10. Thus, the most effective approach to reduction of the disease burden in migrants from high-incidence to low-incidence countries—including latent tuberculosis screening and treatment, active case finding, and improvement of health-care access—is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…This requirement denies the right to enter the country and claim asylum in case of untreated, infectious TB. 51–54 Here, the firewall argument helps to argue for a separation in principle. An empirical investigation as to whether it functions would be the second step.…”
Section: Three Highlights From the Ethics And Justice Literaturementioning
confidence: 99%